Increased Dentin Sensitivity after Scaling Action in Dental Patients - Asridiana Asridiana; Ellis Mirawati; Ernie Thioritz; Bahtiar Bahtiar (Aloha International Journal of Health Advancement (AIJHA), 2024)
Brushing your teeth can't remove tartar, what can remove tartar is scaling. scaling can have a negative impact on the teeth, because previously the teeth were surrounded by tartar, and after scaling there is an empty space in the subgingival area and leaves a wound or scratch on the tooth tissue, causing the tooth to feel sore or painful. This study aimed to analyze the increase in dentin sensitivity after scaling at the Dental Polyclinic, Grestelina Hospital, Makassar. The design of research was one group pretest-posttest. The subjects were 30 patient, selected using accidental sampling technique. Pain before and after the procedure was measured using the Visual Analogue Scale. Data were analyzed using Wilcoxon test. The results of the Wilcoxo test showed a p value = 0.000, so it could be interpreted that there was a difference in the level of dentin sensitivity between before and after the scaling procedure. In this case, after scaling, the sensitivity level becomes increasingly severe. Based on the results of the study, it can be concluded that the scaling action significantly increases the sensitivity of the dentin, so that the pain becomes more severe. Keywords: scaling; dentin sensitivity; pain